Dual‐system tract pattern: Significance for foreland basin reservoir prediction (Jurassic, Central Junggar Basin, West China). (24th June 2019) - Du, Xue‐Bin; Chen, Ping; Lu, Yong‐chao; Song, Xiao‐dong
Abstract : The Junggar Basin is a typical superimposed system characterized by multilateral steep thrusts and extrusions and one of the primary petroliferous basins in Western China. To date, geologists have been most interested in the basin's tectonic evolution and petroleum geology characteristics. Based on field outcrops, lithologic combinations, logging curves, and seismic reflection characteristics, we present a systematic study of the sequence stratigraphy pattern for the Jurassic central Junggar Basin. Herein, we identify the central Junggar area as having a "dual" characteristic sequence framework composed of a lowstand system tract (LST) and a transgressive system tract (TST), which is distinguishable from the traditional three system tract (LST, TST, and highstand system tract [HST]). In each third‐order sequence, the LST consists of conglomerate or pebbly sandstone deposits, displaying the characteristics of braided channel and fan delta. The TST consists of siltstone, argillaceous siltstone, and mudstone, displaying fine‐grained, shore‐shallow lacustrine deposits. It is considered that the combination of multiphasic thrust extrusion and subsequent, steady deposition is likely responsible for the dual‐system tract. The forming process of the dual‐system tract pattern could divide into four stages: the quiet stage of tectonic activity, the early stage of compression, the continuous stage of compression, and the rapid rebound stage. Additionally, two reservoir predictive models are proposed: the progradational predicting model on the edge of the depression and truncated and pinchout predicting model on the palaeo‐uplift. We conclude that the coarse clastic unit of the LST has bright prospects for oil and gas exploration within the superimposed system in Western China.